GaP Homojunction LEDs Fabricated by Dressed-Photon-Phonon-Assisted Annealing. (13th November 2014) - Kim, Jun Hyoung; Kawazoe, Tadashi; Ohtsu, Motoichi
Abstract : By using a homojunction-structured GaP single crystal, we generated a photon energy higher than the bandgap energy (2.26 eV). The device was fabricated by performing dressed-photon-phonon- (DPP-) assisted annealing, while applying a forward-bias current, on a p-n homojunction structure formed by implanting a dopant (Zn) into an n-type GaP substrate. The DPP-assisted annealing increased the light emission intensity in an energy band above 2.32 eV by at least 550% compared with that before annealing.